THE USE OF THE CASE METHOD IN THE FORMATION OF META-SUBJECT COMPETENCIES OF STUDENTS IN CHEMISTRY LESSONS - Umarov, Saidanvar; Sirojov, Farhod (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The formation and diagnosis of the formation of meta-subject skills requires the teacher to have optimal technologies. The latter include case technology. Case technology is a method in which students can have the opportunity to develop a creative personality, communicative competence, the ability to work in a team, the ability to work on an independent task, the ability to act and make decisions in conditions of excess or lack of information. Case technology is an interactive learning technology based on real or fictional situations, aimed not so much at mastering knowledge as at forming new qualities and skills in students. The most common methods of case technology are: analysis of specific situations, situational tasks and exercises, case study.